2014
DOI: 10.1086/677825
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Urinary Catheter Use and Catheter-Associated Urinary Tract Infection: Results from a National Collaborative

Abstract: OBJECTIVE. To examine regional variation in the use and appropriateness of indwelling urinary catheters and catheter-associated urinary tract infection (CAUTI). DESIGN AND SETTING. Cross-sectional study.PARTICIPANTS. US acute care hospitals.METHODS. Hospitals were divided into 4 regions according to the US Census Bureau. Baseline data on urinary catheter use, catheter appropriateness, and CAUTI were collected from participating units. The catheter utilization ratio was calculated by dividing the number of cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 30 publications
6
25
1
Order By: Relevance
“…This comparison clearly explains that catheter utilization is always high in ICU setup and thus the risk of CAUTI in ICU could be proportionately higher. In this study, the incidence of CAUTI was found to be 16 per 100 catheterization which was lesser than the study report of Mahim Koshariya et al , Mangukiya JD et al, Gupta V, et al, Wazait HD et al, Chanda R et al, and Mulhall et al [12][13][14][15][16][17][18][19][20] who reported CAUTI incidence of 27,30.71,36.3,38.75,41,44 per 100 catheterization respectively. Even though its incidence appears lesser, it is not up to the standard of NHSN.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…This comparison clearly explains that catheter utilization is always high in ICU setup and thus the risk of CAUTI in ICU could be proportionately higher. In this study, the incidence of CAUTI was found to be 16 per 100 catheterization which was lesser than the study report of Mahim Koshariya et al , Mangukiya JD et al, Gupta V, et al, Wazait HD et al, Chanda R et al, and Mulhall et al [12][13][14][15][16][17][18][19][20] who reported CAUTI incidence of 27,30.71,36.3,38.75,41,44 per 100 catheterization respectively. Even though its incidence appears lesser, it is not up to the standard of NHSN.…”
Section: Discussioncontrasting
confidence: 59%
“…18,23,24 In the present study, when compared to above-mentioned studies, tuberculosis (25%) was also found to be the other important comorbid condition associated with CAUTI (Fig. 1).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Using electronic alerts, which can assist in reducing CAUTIs [6,12,13] and allow easily accessible audits, was not an option because the hospital's electronic documentation system did not offer such features. Despite the decrease in the proportion of inpatient days with a catheter, the ratio was still quite high (41%) at T2 compared to some other studies [27], where it has been reported to be as low as 10% [28]. Failure to reduce the use of catheters can be explained by two factors.…”
Section: Discussionmentioning
confidence: 70%